Mainstreaming conservation agriculture in Malawi: Knowledge gaps and institutional barriers. (15th June 2017) - Dougill, Andrew J.; Whitfield, Stephen; Stringer, Lindsay C.; Vincent, Katharine; Wood, Benjamin T.; Chinseu, Edna L.; Steward, Peter; Mkwambisi, David D.
Abstract: Conservation agriculture (CA) practices of reduced soil tillage, permanent organic soil coverage and intercropping/crop rotation, are being advocated globally, based on perceived benefits for crop yields, soil carbon storage, weed suppression, reduced soil erosion and improved soil water retention. However, some have questioned their efficacy due to uncertainty around the performance and trade-offs associated with CA practices, and their compatibility with the diverse livelihood strategies and varied agro-ecological conditions across African smallholder systems. This paper assesses the role of key institutions in Malawi in shaping pathways towards more sustainable land management based on CA by outlining their impact on national policy-making and the design and implementation of agricultural development projects. It draws on interviews at national, district and project levels and a multi-stakeholder workshop that mapped the institutional landscape of decision-making for agricultural land management practices. Findings identify knowledge gaps and institutional barriers that influence land management decision-making and constrain CA uptake. We use our findings to set out an integrated roadmap of research needs and policy options aimed at supporting CA as a route to enhanced sustainable land management in Malawi. Findings offer lessons that can inform design, planning and implementation of CA projects, and identify the multi-level institutional support structures required for mainstreaming sustainable land management in sub-Saharan Africa. Highlights: Conservation agriculture remains a contested concept requiring multi-level analysis. An institutional analysis for conservation agriculture in Malawi is provided. We identify knowledge gaps that influence land management decision-making. We provide an integrated roadmap of collaborative research-action partnerships. Collaborative institutional structures are vital for sustainable land management.